1980
DOI: 10.1203/00006450-198010000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Secretory Immunity: Levels of Secretory IgA and Natural Antibodies in Saliva

Abstract: SummaryIn 187 healthy subjects from 2 months to 27 years of age, secretory IgA and free secretory component were assayed in samples of whole saliva obtained before and after stimulation with lemon juice. Antibody titers against Escherichia coli 0 antigens and against rabbit erythrocytes were also dosed in unstimulated saliva. Secretory IgA, undetectable in newborns, was present in all 2-month-olds tested in both unstimulated and stimulated saliva; thereafter secretory IgA levels increased progressively, reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 1 publication
4
53
0
Order By: Relevance
“…Strong correlations over time have been reported for parotid saliva densitometric patterns (Oberg et al, 1982), stimulated parotid saliva concentrations of total protein, lysozyme, lactoferrin, and peroxidase , and unstimulated whole saliva concentrations of amylase, total protein, lysozyme, lactoferrin, peroxidase, and slgA Jenzano et al, 1987;Rudney et al, 1993). There is some uncertainty regarding the stability of slgA, since studies have reported conflicting results (Claman et al, 1967;Stuchell and Mandel, 1978;Burgio et al, 1980;Widerstrom and Bratthall, 1984;Bratthall and Widerstrom, 1985;Rudney et al, , 1993. This may be partly an artifact of sample size, since total slgA has been correlated over time in studies involving larger numbers of subjects (Bratthall and Widerstrom, 1985;Gleeson et al, 1991;Rudney etal, 1993).…”
Section: (B) Longitudinal Variationmentioning
confidence: 98%
“…Strong correlations over time have been reported for parotid saliva densitometric patterns (Oberg et al, 1982), stimulated parotid saliva concentrations of total protein, lysozyme, lactoferrin, and peroxidase , and unstimulated whole saliva concentrations of amylase, total protein, lysozyme, lactoferrin, peroxidase, and slgA Jenzano et al, 1987;Rudney et al, 1993). There is some uncertainty regarding the stability of slgA, since studies have reported conflicting results (Claman et al, 1967;Stuchell and Mandel, 1978;Burgio et al, 1980;Widerstrom and Bratthall, 1984;Bratthall and Widerstrom, 1985;Rudney et al, , 1993. This may be partly an artifact of sample size, since total slgA has been correlated over time in studies involving larger numbers of subjects (Bratthall and Widerstrom, 1985;Gleeson et al, 1991;Rudney etal, 1993).…”
Section: (B) Longitudinal Variationmentioning
confidence: 98%
“…25 sIgA levels, which are undetectable in newborns, increase progressively and reach adult values in stimulated saliva by 2 to 4 years of age and, in unstimulated saliva, by 6 to 8 years of age. 26 In contrast, salivary IgG is primarily derived from serum via gingival crevicular fluid (GCF) and is present in low concentrations. Consequently, the IgG concentration in saliva should increase as inflammation of the periodontal tissues becomes more severe and vascular permeability increases, resulting in increased flow of GCF.…”
Section: Jaypeementioning
confidence: 99%
“…The full protective potential of secretory IgA is not present in the infant at birth [4,5]. Adult levels of secretory IgA are not reached until after 1 year of age [6,7]. It has been suggested that in infants the presence of IgM compensates partially for the low levels of IgA [7].…”
Section: Introductionmentioning
confidence: 99%